2017
DOI: 10.1039/c6ra27263k
|View full text |Cite
|
Sign up to set email alerts
|

The effects of NaF concentration on electrochemical and corrosion behavior of AZ31B magnesium alloy in a composite electrolyte

Abstract: Electrochemical and corrosion behavior of AZ31B magnesium alloy have been investigated in composite solution of MgSO4–Mg(NO3)2 (0.14 mol L−1 MgSO4, 1.86 mol L−1 Mg(NO3)2) under different sodium fluoride (NaF) concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 41 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…However, instead a potential shift in the negative direction was observed as the BL number increases. This behavior was reported with alloys containing magnesium, 25 aluminium, 26 aluminium alloys 27 and ferrous materials. 28 No significant changes were observed in the cathodic branch of the Tafel plot for 1 BL and 4 BL samples, indicating that the corrosion protection effect is based on the suppression of anodic metal dissolution resulting in a negative shift of the free corrosion potential.…”
Section: Electrochemical Analysis Of the Model Coatingssupporting
confidence: 62%
“…However, instead a potential shift in the negative direction was observed as the BL number increases. This behavior was reported with alloys containing magnesium, 25 aluminium, 26 aluminium alloys 27 and ferrous materials. 28 No significant changes were observed in the cathodic branch of the Tafel plot for 1 BL and 4 BL samples, indicating that the corrosion protection effect is based on the suppression of anodic metal dissolution resulting in a negative shift of the free corrosion potential.…”
Section: Electrochemical Analysis Of the Model Coatingssupporting
confidence: 62%
“…The conventional epoxy coating does not contain strong acceptor functional groups and is also easy to peel out from the alloy surface due to which the grain boundary of epoxy coated Mg alloy was affected which in turn is due to the intergranular corrosion, as shown in the above surface studies of epoxy coated Mg alloy surface. [46][47][48][49][50][51] However, Mg alloy coated by the Tb functionalized graphene oxide showed that the propagation of pitting corrosion stops due to the changes in the electron ow of Tb 3+ between the alloy surface and electrolyte medium. Due to this, the corrosion current decreased and corrosion potential increased.…”
Section: Corrosion Inhibition Studiesmentioning
confidence: 99%
“…1(d)) are located at 50.4 eV, which is a characteristic value for the Mg 2+ oxidation, as reported earlier. 37,38 The structural morphology of the ZnO/MgO/Cr 2 O 3 NFs analyzed by FESEM…”
Section: Xps Analysis Of the Zno/mgo/cr 2 O 3 Nfsmentioning
confidence: 99%